Video endoscopic inguinal lymphadenectomy and open inguinal lymphadenectomy for penile cancer in China: a systematic review - Du, Jiang-Ping; Lamichhane, Nirmal (Nepalese Journal of Cancer, 2018)
Background: To evaluate the effect between video endoscopic inguinal lymphadenectomy (VEIL) and open inguinal lymphadenectomy (OIL) for penile cancer to provide the evidence-based basis for the selection of the clinical therapy schemes. Methods: The related clinical controlled trial literatures on the effective comparison of VEIL and OIL were retrieved from the databases of CNKI and Wanfang database. The screening was independently performed by reviewer according to the including and excluding criteria. The related data were extracted and the meta-analysis performed by the RevMan 5.3 software. Results: A total of 9 trials were included. There were 335 cases of inguinal lymphadenectomies, in which 151 cases were VEIL and 184 cases were OIL. The meta-analysis results showed that there were no statistical differences between the two types of operations in terms of the operative time (WMD=28.74, 95% CI-4.12 61.60, P=0.09), but the difference between VEIL and OIL in term of intra-operative blood loss (WMD=-29.24, 95% CI–55.24 - 22.89, P<0.01), postoperative hospital stays (WMD=-3.43, 95%CI–5.07 -1.80, P<0.01), postoperative drainage time (WMD=-3.81, 95%CI–5.38 -2.23, P<0.01), surgical complications (Number of sides OR=0.53, 95% CI0.34 0.81, P<0.01; Number of cases OR=0.36, 95% CI0.24 0.54, P<0.01). Conclusion: VEIL has approximately the same time of operation to OIL, but has less intra-operative blood loss, hospital stay, postoperative drainage time and surgical complications.